The Research of Competitiveness of Lithuanian Consumers’ Co-Operation and its Increasent Perspectives - Vengrauskas, Vytautas; Rūgytė, Ramunė (Ekonomika, 2002)
For the research of competitiveness of Lithuanian consumers’ co-operation M. E. Porter competitive advantage model modified for co-operative sector was used. Based on this model matrix for evaluation of competitiveness of consumers’ co-operation was created. The research of consumers co-operative members, questioning of 47 co-operatives’ directors and a member of Lithuanian consumers co-operation union enabled to identify the strengths and the weaknesses of individual factors. In this article the means for the competitiveness increasement, associated with improvement of system’s wholesale, co-operative image, members’ loyalty to co-operative increasement were presented.